Modern understanding of comorbidity and approaches to formulating the diagnosis of comorbid patients - А. L. Vertkin; O. V. Zayratyants; A. L. Kebina; M. M. Shamuilova; G. Yu. Knorring (Лечащий Врач)
Background. Comorbidity as the presence of two or more pathological processes in a patient is one of the most discussed topics in medical forums around the world and in Russia. Meanwhile, the breadth of discussion of this problem carries the risk of losing the true meaning of comorbidity, set out by the ideologist of this problem, A. R. Fainstein, namely: a combination in one patient of two and/or more chronic diseases, pathogenetically interrelated. (with an unconditional understanding of the variety of options for these connections).Results. This article offers the reader a detailed look at comorbidity in its original/true understanding, based on a deep understanding of the pathogenesis of diseases and pathomorphological analysis of completed cases of comorbidity. Various options for comorbidity (causal, complicated, iatrogenic, specified and unspecified) with pathomorphological confirmation are considered. Pathomorphological illustrations of the analyzed variants are offered – preparations from the clinical and morphological archive of the Department of Therapy, Clinical Pharmacology and Emergency Medical Care of the Moscow State Medical and Dental University (now the Russian University of Medicine). Inseparable from the understanding of comorbidity is an accurate, uniform presentation of diagnoses – clinical and pathomorphological – by doctors of all specialties, to ensure continuity in the provision of medical care and improve the quality of diagnosis and treatment. The article updates the rules for formulating a clinical and pathomorphological diagnosis in a comorbid patient, namely: a clear reflection of the presence of the main disease and comorbid ones (competing, combined and background diseases), complications of the main disease and concomitant diseases. In the finale, algorithmized "comorbidity postulates" are proposed, facilitating the perception and use of the proposed methodological approaches.